New ways of studying emotions in organizations - Ha<U+0308>rtel, Charmine E. J., 1959-; Zerbe, W. J.; Ashkanasy, Neal M., 1945- (Research on emotion in organizations ;, 2015)
The rapidly growing recognition of the importance of emotions in understanding all aspects of organizational life is facilitating the development of focused areas of scholarship. Chapters in this volume are authored by leading and emerging scholars of emotion in organizational settings from around the world and deal with new ways of looking at emotions within the organizational framework.